Egg-Laying Competition and Maternal Effects in a Plural-Breeding Joint-Nesting Bird - Schmaltz, Gregory U. (My University, 2008)
I investigated the maternal effects that take place in a joint-nesting bird: the smooth-billed ani. Female anis were shown to respond to increasing group size by increasing the number of eggs produced per capita, by tossing and burying more eggs per capita, and by taking longer to reach the dedicated incubation phase. These results support the hypothesis that females respond to increased egg laying competition by trying to skew the contents of the final incubated clutch of eggs in their own favor. I showed that in ani groups, yolk testosterone and estradiol deposited by females in eggs increased from early- to late-laid eggs. Increases in yolk steroid levels over the laying sequence may function to mitigate the disadvantage of being a later-hatched chick. This maternal influence may not be a mere reflection of a female's hormonal status as female plasma circulating levels of testosterone and estradiol did not vary in the same direction as yolk hormone profiles. I showed that yolk corticosterone levels, an indicator of maternal physiological stress, increased with laying order in multi-female groups, but not in single-female groups. Results suggest that laying females experience higher levels of stress in multifemale groups. The above results suggest that communal life in anis generates competition and egg production waste that likely reduces short-term per capita reproductive benefits. Female anis can vary egg quality via deposition of hormones in eggs, and also lay eggs of different sizes. I showed that circulating plasma testosterone levels were higher in nestlings with better begging abilities. Furthermore, nestlings hatched from eggs laid late in the laying sequence had better begging abilities. These results suggest that testosterone is an important controlling mechanism of begging behaviour, and that female testosterone depositions in eggs rave long lasting effects on offspring development and behavior.
Maternal Effects in a Joint-Nesting Bird
Keywords: egg-laying; maternal effects; plural-breeding; joint-nesting bird